SOSIALISASI PENINGKATAN PENGETAHUAN JAJANAN SEHAT SEBAGAI UPAYA PERBAIKAN STATUS GIZI PADA SISWA di SDN 011 PANCURAN GADING KAMPAR - Novia Nazirun; Dea Mustika; Yulia Tri Lestari (Bajang Institute, 2022)
Snacks at school are indeed varied and more interesting than lunches brought from home, but these interesting snacks are actually poor in nutrition and far from healthy. Snacks sold by traveling vendors are often in front of the school environment. The content of borax and formalin still dominates the content of harmful substances in children's snacks at schools. In connection with this phenomenon, there is a need for socialization regarding the types, processing, and feasibility of consuming snacks that are widely sold so that children can understand so that they can choose and differentiate between healthy and unhealthy snacks.